Charcoal Briquette Making Training Based on Sacha Inchi (Plukenetia volubilis) Skin Waste in Banyurip Village, Sragen: Pelatihan Pembuatan Briket Arang Berbasis Limbah Kulit Sacha Inchi (Plukenetia Volubilis) di Desa Banyurip, Sragen - Sulthan Rafli Sya’ban Ramdhani; Jihan Ismahwati; Shanly Rizki Sahara; Ririn Ambarwati; Yus Andhini Bhekti Pertiwi; Ana Agustina; Supriyadi; Sigit Murhofiq (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The charcoal briquette making training activity was carried out in Banyurip Village, Jenar District, Sragen Regency, Central Java. The community in Banyurip Village through the Banyurip Lestari Forest Village Community Institution (LMDH) manages Sacha Inchi (Plukenetia volubilis) bean agricultural products. The plant is used to be processed into various products with economic value. However, the waste produced from the Sacha Inchi seed processing process has not been managed optimally. The purpose of this training activity is for the community to know how to make briquettes so that they can utilize Sacha Inchi skin waste. The implementation of the training was carried out through the stages of coordination, preparation, training, and evaluation of activities. There were 16 participants who attended the training who were members of the Banyurip Lestari LMDH. The results of this activity showed that charcoal briquette making training was something new for some participants. Through this activity, it is hoped that the community's capacity in utilizing Sacha Inchi skin waste will increase and lead to prosperity.